2017
DOI: 10.21873/anticanres.11323
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy in Patients with Lung Oligometastases from Colorectal Cancer

Abstract: SBRT can be considered as local therapy in patients with lung metastases from CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…They also concluded that local control rates following 48 Gy in 4 fractions were significantly worse in metastatic lung tumors when compared with stage I primary lung cancer, and suggested increasing the SBRT dose for metastatic lung tumors. Several retrospective studies published recently also demonstrated colorectal cancer lung metastases are associated with a higher hazard of local failure and require higher radiation doses [ 42 , 43 , 48 , 49 , 54 , 55 ]. The results of these studies are summarized in Table 3 .…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that local control rates following 48 Gy in 4 fractions were significantly worse in metastatic lung tumors when compared with stage I primary lung cancer, and suggested increasing the SBRT dose for metastatic lung tumors. Several retrospective studies published recently also demonstrated colorectal cancer lung metastases are associated with a higher hazard of local failure and require higher radiation doses [ 42 , 43 , 48 , 49 , 54 , 55 ]. The results of these studies are summarized in Table 3 .…”
Section: Discussionmentioning
confidence: 99%
“…With currently available minimally invasive treatments, it has now become possible to control recurrent lung metastases by local treatment and to delay the emergence of end-stage symptoms. In recent years, three-dimensional stereotactically guided local treatments such as radiofrequency ablation, stereotactic body radiation therapy (SBRT), and 125 I seed implantation, have achieved good results in the treatment of pulmonary metastases [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Purposementioning
confidence: 99%
“…Furthermore, with the development of anticancer drugs and immunotherapy, long-term survival has been obtained even in cases with distant metastases. As several papers report the usefulness of SBRT for 'oligo-metastasis or oligo-recurrence,' SBRT is expected to play a role as radical local therapy for pulmonary oligo-recurrence (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%